PENGARUH PERPUTARAN KAS DAN PERPUTARAN PIUTANG TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR - Yusuf, Deisya Muhrima Aulia (Universitas Prof.Hazairin,SH Bengkulu, 2023)
The study aims to determine the effect os cash turnover and accounts recevaible turnover on profitability. The population in this tudy are food and berevage sub sector companies listed on the Indonesia Stoch Exchange for the period 2019-2021. The sampling method that will be uses is purposive sampling, a sample of 30 saompanies that match the criteria. The research method used is quantitative descriptive with stastical analysis. The hypothesis test that will be used is a partial test and result of this study partially show that cash turnover has an effect on profitability with the result tcount 4.094 > table 1.988 meaning H1 is accepted, pastially accounts receivable turnover has an effect on profitability with a result of 4.092 > table 1.988 meaning H2 is accepted. But simultaneously cash turnover and accounts recevaible turnover affect profitability with a Fcount of 15.763 > table 3.101. simultaneous influence is shown in the result of the coefficient of determination (R2) of 26,6% but the rest is I nfluenced by other factors.